Epidemiological assessment of parasitic infections in poultry farms of Thi Qar province:Prevalence, intensity, and associated risk factors - ali, zainab Ali Hussein; Zaman Subhi. Madlool2 (University of Thi-Qar Journal of agricultural research, 2025)
Parasitic infections represent the main causes of mortality of livestock animals. However, the current study investigates the prevalence and intensity of parasitic infections in poultry across various age groups and farming systems within Dhi Qar Province, Iraq. A total of 1,405 birds were analyzed through veterinary records and parasitological assessments. The study identified several parasites, with Ascaridia galli being the most prevalent at 35.0% and an average intensity of 20.0 ± 7.5 worms per infected bird. Other significant parasites included Heterakis gallinarum, Capillaria spp., Raillietina spp., and Eimeria spp. Notably, the burden of parasites and oocyst counts increased with the age of the birds, with adult birds showing significantly higher intensities compared to chicks (P < 0.05). Seasonal variations were also evident, with prevalence peaking in spring at 50.0% and dropping to 30.0% in winter. Additionally, open-sided, floor-reared systems exhibited a higher prevalence of parasites compared to closed cage systems (60.0% vs 30.0%; p < 0.001). Statistical analyses confirmed that age, season, and farm management practices are critical factors influencing infection risk. Our study findings underline the widespread and age-dependent characteristics of parasitic diseases in livestock animals, emphasizing the need for focused management techniques to improve poultry health and productivity in the region